Analisis Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2022 - Ika Soleha (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
: The share price is the closing price during the observation period and is very dependent on economic conditions, political conditions and the company's performance. Share price movements are determined by demand and supply from investors. When demand is greater than supply, prices will tend to rise. The aim of this research is to find out whether financial performance as measured by the financial ratios current ratio, return on equity, debt to equity ratio, and earnings per share have a significant effect on stock prices. The method used is t test analysis and f test. The samples taken were 10 companies using a purposive sampling method with an observation period of 4 years. The results of this research show that partially only earnings per share have a significant effect on stock prices, while simultaneously it shows that the four variables, namely CR, ROE, DER, and EPS have a significant effect on stock prices.